Tunis als Laboratorium osmanischer Modernität: das Beispiel der Vorstadtbahn (1863-1881). - Lafi, Nora (Deutsches Institut für Urbanistik, 2018)
Der Beitrag untersucht die Modernisierung der Transportinfrastruktur dieser osmanischen Provinzhauptstadt. Sie fokussiert auf die Bahnstrecke, die Stadt und Hafen verband und deshalb für die wirtschaftliche Entwicklung von Tunis von größter Bedeutung war. Die Tatsache, dass die Strecke durch einen ausländischen Konzessionsnehmer gebaut wurde, machte sie zum Kristallisationspunkt geopolitischer Spannungen. Die Einmischung Frankreichs, Großbritanniens und Italiens unterstreicht die Ambivalenz dieser Form der städtischen Modernisierung.

This article discusses the way in which infrastructural modernization was implemented in late-Ottoman Tunis. Based upon research in the national archives of Tunisia, it follows the various steps of the planning, construction and operation of a suburban railway between the 1850s and the turn of the 20th century: concession to foreign private investors, rivalries between foreign consulates as for the control of infrastructures in the Ottoman province of Tunisia, passage to the colonial period. The article illustrates both the genuine character of the local Ottoman effort at infrastructural modernization and its founding ambiguities, i.e., the recourse to the system of the concession, constant interferences by foreign powers (British, French and Italian). lt also illustrates how modernization was the result not of a mere import of foreign expertise but also of negotiations of the local level and of a planned policy at the imperial level with peer-to-peer circulations between the main cities of the Empire.
Keywords: Stadtgeschichte; Selbstverwaltung; Verkehrsinfrastruktur; Eisenbahn; Transport; Hafenstadt; Wirtschaftsentwicklung; Konzession; Transformation; Modernisierung; Güterverkehr; Konzessionsvergabe